PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PANCASILA MELALUI MODEL PEMBELAJARAN GAME BASED LEARNING - Rouzatul Jannah, Rouzatul Jannah; Hasanah, Hasanah; Asih Winarty, Asih Winarty (Yayasan Darul Hasanah Aceh, 2024)
The achievement of learning outcomes can be seen from student learning outcomes. Learning will be enjoyable if there is an atmosphere that is relaxed, safe and comfortable, interesting, free from pressure, there is full involvement, an interesting learning environment, enthusiasm, feelings of joy and high concentration. Therefore, a learning model is needed that can improve student learning outcomes. Therefore, the game based learning model is a learning model that is carried out through games by distributing crossword puzzle sheets to each student. The aim of this research is to determine whether the game based learning model using crossword puzzles will improve student learning outcomes on Pancasila material, namely on Pancasila values ​​in everyday life for class X. Data collection in this research was carried out using test questions in the form multiple choice and observation sheet. For student learning outcomes on Pancasila material, the value in the control class with a score of 61.39% is classified as